A Proposal for Data Registry system for Urologic Cancers in Iran - Simforoosh, Fatemeh; Simforoosh, Nasser; Dadpour, Mehdi; Radfar, Mohammad Hadi (Urology Journal, 2021)
Purpose: Data registries are organized systems that facilitate collection, storage, and analysis of data related to a specific disease in a defined population. Here we introduce a data registry system which was designed to cover the four most common urologic cancers (prostate, bladder, renal and testis). Materials and methods: All contributing centers can enter data into the system after logging in with their unique usernames and passwords. In this system, the information of each individual patient will be entered in several structured forms covering various steps of management of the patients. Results: Our proposed registry is an interactive, web-based database designed to collect complete data of patients with common urological cancers. We devised a council that functions as the central committee that will initiate, supervise, and monitor all steps of the projects including data collection, data audit, as well as data analysis and publication. To facilitate manuscript publication, the system will provide assistance and support throughout all the steps of statistical analysis and manuscript preparation. Conclusion: This proposed registry can have a national target and is designed to provide evidence-based information that could support strategic planning and national multi-centric studies.